Profitabilitas Dan Leverage: Apakah Berperan Dalam Memprediksi Tax Avoidance? - Wiriatmaja, Nuraini Ulya; Agus Satrya Wibowo; Ricky Yunisar Setiawan; Simamora, Lamria (LPPM POLITEKNIK LP3I BANDUNG, 2025)
The purpose of this study is to analyze the role of Profitability and Leverage in predicting Tax Avoidance in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. The research method applied is a quantitative method with multiple linear regression approaches. This study uses a population of 59 companies with a total sample of 295. The data utilized is secondary data in the form of annual financial reports of manufacturing companies published during the 2019-2023 period. The results prove that profitability negatively affects tax avoidance. Meanwhile, leverage affects tax avoidance positively and significantly. Profitability and leverage have an impact in predicting tax avoidance positively, simultaneously and significantly.